PENGARUH MOTIVASI INTRINSIK TERHADAP KINERJA PERAWAT PELAKSANA DI RUMAH SAKIT TK. IV PEMATANG SIANTAR - Muchti Yuda Pratama (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2017)
ABSTRACT Service quality was assessed based on five dimensions: reliability, tangibles, assurance, and empathy. Decreased performance of nurses who took place at the Hospital Tk. IV Pematang Siantar due to decreased intrinsic motivation such as achievement, recognition, responsibility, opportunity to advance and the work itself that affect the performance of nurse executor.         This study aimed to analyze the influence of intrinsic motivation on the performance of nurses in Hospital Tk. IV Pematang Siantar in 2017. This type of research used analytic survey research method. The population was all implementing nurses who number 97 nurses. The number of samples were 61 nurses who were obtained by purposive sampling. Data analysis was done by using linear regression test.         The results showed that there was an effect of intrinsic motivation on the performance of nurse executor (p <0,05). The most dominant variable to the performance of the nurse was the work itself which has the greatest coefficient value. The conclusion of this research that there was a significant influence of intrinsic motivation on the performance of nurse executor at Hospital Tk. IV Pematang Siantar.         Recommended to Head of Hospital Tk. IV Pematang Siantar in order to motivate their employees, especially the implementing nurses to improve performance for the improvement of the work. Keywords: intrinsic motivation, performance, nurses